2017
DOI: 10.1038/srep40185
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of pressure therapy (15–25 mmHg) for hypertrophic burn scars: A systematic review and meta-analysis

Abstract: Although pressure therapy (PT) represents the standard care for prevention and treatment of hypertrophic scar (HS) from burns, its practice is largely based on empirical evidence and its effectiveness remains controversial. To clarify the effect of PT (15–25 mmHg) for HS, we performed the systematic review and meta-analysis. Several electronic databases were screened to identify related randomized controlled trials (RCTs). 12 RCTs involving 710 patients with 761 HS resulting from burn injuries were included. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(45 citation statements)
references
References 49 publications
1
44
0
Order By: Relevance
“…Clinically, there are reports that paper tape reduces scar volume significantly and reduces mechanical tension, which results in minimal scar formation (Atkinson et al, 2005;Rosengren et al, 2013). A meta-analysis also indicated that pressure therapy was effective for hypertrophic scar patients, improving pigmentation, and redness and even reducing scar coloration (Ai et al, 2017).…”
Section: Primary Cilia-targeted Anti-fibrotic Therapeutic Approachesmentioning
confidence: 99%
“…Clinically, there are reports that paper tape reduces scar volume significantly and reduces mechanical tension, which results in minimal scar formation (Atkinson et al, 2005;Rosengren et al, 2013). A meta-analysis also indicated that pressure therapy was effective for hypertrophic scar patients, improving pigmentation, and redness and even reducing scar coloration (Ai et al, 2017).…”
Section: Primary Cilia-targeted Anti-fibrotic Therapeutic Approachesmentioning
confidence: 99%
“…It was recently reported that the incidence of hypertrophic scars in burn patients in China reached 90% (3). Scar formation affects a patient's appearance, and results in contracture that may lead to different degrees of dysfunctions including tendon contracture, joint dislocation and dyskinesia (4,5). At present, the pathogenesis of hypertrophic scar has not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…This is problematic as researchers may be unaware of the conceptual underpinnings of the aspect of burn scarring they selected to investigate, thus resulting in poor validity or a lack of comprehensiveness when measuring the impact of interventions on burn scarring. For example, two recent systematic reviews investigating the effectiveness of scar massage [7] and pressure garments [8] on characteristics of burn scarring identified only one shared outcome of interest (vascularity) across the two studies. Within the clinical environment, the use of diverse terminology and inconsistent definitions of burn scarring can result in confusion and inconsistencies in assessment and treatment provision, including a focus by health professionals on the physical features of a scar alone.…”
Section: Introductionmentioning
confidence: 99%